DOCENTES DO ENSINO SUPERIOR – GESTÃO DA CARREIRA NA FASE PRÉ-APOSENTADORIA - Cristiane Buhamra Abreu (Universidade Federal de Santa Catarina, 2018)
The article addresses issues related to the teaching career management in the face of the aging of the Brazilian population. It aims to understand how higher education teachers manage their careers when they are about to retire. The theory is based on the Teacher's Professional Life Cycle (Huberman, 1989), which divides the teaching career into phases, from the beginning to the divestment. This is a qualitative research carried out in a private higher education institution, with individual interviews with the teachers when they are about to retire and / or those who are retired, but who continue to teach. The findings point to three types of teaching career and one can perceive, in general, the lack of planning of the researched ones for the management of their careers. It is concluded that the teaching career has particularities that illustrate the challenges of the management of long and multiple careers, which are those that are likely to describe the path of professionals in the near future.